The River Civilization of the Balinese and Dayakese Legends: A Comparative Study on Anthropological Linguistics - Maria Arina Luardini; Putu Sutama; Natalina Asi (Pusat Kajian Bali Universitas Udayana, 2016)
Legend is a kind of traditional knowledge which consists of various explanations reflecting the ethnic world views and social practices of a community. It is also considered as a very simple knowledge product of traditional community although it sometimes has very broad meanings. Legend texts of Tirta Solas and Tampara Tatum belonging to the Balinese and the Dayakese (Dayak Ngaju people) in Central Kalimantan, which use rivers as the setting of stories, can reveal the embryonic knowledge of local cultures. Based on anthropolinguistics, this article discusses the river civilizations of the two ethnic groups which have socio-cultural similarities and differences in religious systems – as the two native ethnic community groups share the livelihood of taking advantages of a river and practice the Hinduism based – the Balinese refers to India and the Dayakese to native people beliefs; social organization, which also influences their arts closely related to their beliefs; and livelihood system in taking advantages of a river.